Thin film technology handbook - Elshabini-Riad, Aicha (Electronic packaging and interconnection series, 1998)
The most comprehensive source available on the preparation, characterization, and emerging applications of thin film. This book features extensive new advances applied in multichip modules (MCMs), and covers the basic principles and applications of thin film deposition techniques for practical use. It provides and develops design guidelines to realize multilayer structures in microcircuits, thus addressing a critical and rapidly growing area.